Early life risk factors for testicular cancer: a case-cohort study based on the Copenhagen School Health Records Register. (1st February 2017) - Piltoft, Johanne Spanggaard; Larsen, Signe Benzon; Dalton, Susanne Oksbjerg; Johansen, Christoffer; Baker, Jennifer L.; Cederkvist, Luise; Andersen, Ingelise
Abstract: Purpose: One established risk factors for testicular cancer is cryptorchidism. However, it remains unclear whether cryptorchidism is a risk factor in itself or whether the two conditions share common causes in early life (estrogen hypothesis), such as birth weight and birth order. The objective of this study is to utilize data from the Copenhagen School Health Records Register (CSHRR) to evaluate cryptorchidism, birth weight and birth order as risk factors for testicular cancer. Methods: The study population consisted of 408 cases of testicular cancer identified by a government issued identification number linkage of the entire CSHRR with the Danish Cancer Registry and a random subsample of 4819 males from the CSHRR. The study design was case-cohort and the period of follow-up between 2 April 1968 and 31 December 2003. Results: Cryptorchidism was significantly associated with testicular cancer in crude analyses [hazard ratio (HR) = 3.60, 95% CI 2.79–4.65]. Birth weight was inversely associated with testicular cancer and no clear association with birth order was observed. The positive association between cryptorchidism and testicular cancer was only slightly attenuated controlling for birth weight and birth order and stratified on birth cohort (HR = 3.46, 95% CI 2.67–4.48). Conclusion: This study confirmed the robustness of the association between cryptorchidism and testicular cancer even after adjustment for birth weight and birth order. Furthermore, the study showed an inverse association between birth weight and testicular cancer.